Founder of Hasidism a quest for the historical Ba'al Shem Tov - Rosman, Moshe 1949- (Contraversions, 1996)
Rosman's study casts a bright new light on the traditional stories about the Besht, confirming and augmenting some, challenging others. Most important, it overturns the widespread belief that the Ba'al Shem Tov was a religious revolutionary and a rebel against the clerical and communal establishment. Rosman finds, on the contrary, that the Besht was quite representative of the existing social, religious, and political order, a holy man who conformed to expected patterns of behavior. The evidence indicates that he made moderate changes, which led eventually to the development of Hasidism's mature institutions